Monitoring of interactions of a monumental historical complex located on an earth embankment - Miedzialowski, Czeslaw; Malesza, Jaroslaw; Malesza, Mikołaj; Ustinovichius, Leonas (Journal of Civil Engineering and Management, 2014)
The Camaldolese Monastery was built in the seventeenth-century on a man-made hill raised on a Wigry lake is land in the north-eastern part of Poland. Over the following two hundred years, the Monastery buildings were subjected to destructive weathering processes and underwent significant demolition during the two World Wars. Subsequently, the complex was reconstructed and renewed. All the Monastery buildings were raised on two earth terraces varying in height from 6 to 8 m. The terraces were formed of crushed bricks and stone debris that filled up the underground structures built earlier. The hill is composed of different geotechnical layers and their influence on the stability of the whole hill, displacement and deformation of the buildings have been monitored. The results of the monitoring are presented in the paper. The thickness of backfilled soil layers varies from 1 to 5 m and an assessment of layer parameters is influencing the actual state and future renovation of the Monastery buildings. In 2004, the Monastery buildings were affected by dynamic forces of an earthquake that measured 5.3 on the Richter scale despite the fact that this region had never been subjected to any seismic hazards. As a result, larger than expected deformations of the sub-base caused excessive cracking of the buildings and destruction of existing water and sewage system.